Isu Tubuh Perempuan dalam Post terkait NoBra Day Melalui Sudut Pandang Feminisme Posmodern - Putri, Margarita Febrica Nonga (UI Scholars Hub, 2015)
Woman’s body is an issue in No Bra Day movement in the social media, basically, mobilizes female netizens to fight breast cancer together by taking off their bras for a day. As it started globally on October 13th, 2013, this movement attracts pro and contra reaction. The responses are linked by the use of related hash tags. As exposing women’s body to the public sphere considered as uncommon, this movement is oftentimes underestimated. On the contrary, this movement brings a new meaning on woman’s body. This encoded meaning cannot be absorbed thoroughly by the female netizens because of the patriarchal construction. The achieved meaning cannot be one hundred percent as it aims to. Furthermore, the decoded meaning still shows the affirmation to patriarchal order. As a media product, the reception theory of Stuart Hall and postmodern feminism of Luce Irigaray are used to examine the new meaning interpreted and reflected in the responses, which also show the affirmation or even internalization to the patriarchal order.